String Processing and Information Retrieval 16th International Symposium, SPIRE 2009 Saariselk,̃ Finland, August 25-27, 2009 Proceedings - Karlgren, Jussi.; Tarhio, Jorma.; Hyyr,̲ Heikki. (Lecture Notes in Computer Science,, 2009)
This book constitutes the refereed proceedings of the 16th String Processing and Information Retrieval Symposium, SPIRE 2009 held in Saariselk,̃ Finland in August 2009. The 34 revised full papers were carefully reviewed and selected from 84 submissions. The papers are organized in topical sections on algorithms on trees, compressed indexes, compression, indexing, content analysis, string algorithms and bioinformatics, string algorithms and theory, and using and understanding usage.